2021
DOI: 10.1007/s00125-021-05509-0
|View full text |Cite
|
Sign up to set email alerts
|

HDL and type 2 diabetes: the chicken or the egg?

Abstract: HDL is a complex macromolecular cluster of various components, such as apolipoproteins, enzymes and lipids. Quality evidence from clinical and epidemiological studies led to the principle that HDL-cholesterol (HDL-C) levels are inversely correlated with the risk of CHD. Nevertheless, the failure of many cholesteryl ester transfer protein inhibitors to protect against CVD casts doubts on this principle and highlights the fact that HDL functionality, as dictated by its proteome and lipidome, also plays an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 86 publications
0
46
1
1
Order By: Relevance
“…Nevertheless, contrasting findings have also been reported [ 155 , 156 ]. There seems to be a bidirectional relationship between T2D and HDL whereby diabetes could also modulate the composition and function of HDL [ 157 ]. Concentration of large HDL particle and HDL particle size have been found to be increased in patients with T1D compared with participants without diabetes, while small HDL and total HDL particle concentration were reduced [ 158 ].…”
Section: Metabolomics In Cardiovascular Diseasementioning
confidence: 99%
“…Nevertheless, contrasting findings have also been reported [ 155 , 156 ]. There seems to be a bidirectional relationship between T2D and HDL whereby diabetes could also modulate the composition and function of HDL [ 157 ]. Concentration of large HDL particle and HDL particle size have been found to be increased in patients with T1D compared with participants without diabetes, while small HDL and total HDL particle concentration were reduced [ 158 ].…”
Section: Metabolomics In Cardiovascular Diseasementioning
confidence: 99%
“…Our previous work has suggested that HDL dysfunction including cholesterol efflux capacity and inhibitory on endothelial lipase existed in patients with T2DM [ 14 ]. Some investigators have explored the possible mechanism of the reduction of HDL level and its function in T2DM [ 15 , 16 ]. Our further research has showed that patients with T2DM have a lower serum HDL level and different components compared with non-T2DM patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, HDL-C can reflect genomic changes, for example, changes in HMGCR polymorphisms can lead to a reduction in HDL-C, which is thought to be associated with the risk of T2DM ( 36 ). ABCA1 gene variants are capable of contributing to T2MD development by reducing HDL-C levels leading to β-cell lipotoxicity ( 37 ). In addition to concentration, the particle size of HDL has been proved to be associated with the maintenance of glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%